Second partition: fault-lines in India's democracy - Patwant Singh (New Delhi, 2007)
A fearless and incisive commentary on twenty-first century India and the problems that imperil its future... INDIA is the world's second-fastest growing economy, but one in every four of its citizens lives on less than a dollar a day. While the nation boasts of having more dollar millionaires than the United States, it also has the highest number of maternal deaths in the world. India, an emerging global power, is a country deeply divided. Unsparing in its study of the country's grim realities, The Second Partition is a bold critique of post-Independence India. At a time when the nation is at a crossroads, this volume is an invaluable and necessary wake-up call for its leadership and its citizens.
Keywords: Democracy-India